ANALYSIS OF CRYSTAL STRUCTURE AND FUNCTIONAL GROUPS OF NiFe2O4 USING SOL GEL METHOD - Mashadi Mashadi; Yunasfi Yunasfi; Wisni Ari Adi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2016)
ANALYSIS OF CRYSTAL STRUCTURE AND FUNCTIONAL GROUPS OF NiFe2O4 USING SOL GEL METHOD. A synthesis and characterization NiFe2O4 with sol gel method have been conducted. Fe2(NO3)3.9H2O powder mixed with Ni(NO3)2 was dissolved in 50 ml of polyethylene glycol at room temperature, then heated at a temperature of approximately 60 °C for 1 hour while stirring to form a wet gel. The gel was then dried in an oven at 120 °C for 5 hours and grinded to form a powder NiFe2O4. NiFe2O4 powder was then heated with a furnace at a temperature variation of 400°C, 600 °C, 800 °C and 1000 °C for 5 hours respectively. X-Ray Diffraction (XRD) pattern indicates that in this stage the sample is single phase. Fourier Transform Infra Red (FT-IR) spectroscopy analysis showed two absorption bands in the range of 411 and 599 cm-1 related to octahedral and tetrahedral sites.